HUKUM PERLINDUNGAN KESELAMATAN DAN KESEHATAN KERJA (K3) BAGI PEKERJA PEMADAM KEBAKARAN PEMERINTAH KOTA MADIUN - Dhazeng Murwiyandono; Diding Rahmat (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2024)
This research discusses legal protection related to occupational safety and health (K3) for employees at the Madiun City Government Fire Department agency. Firefighters have a very important role in protecting the public from the dangers of flames (fires). However, work carried out in full carries risks such as exposure to smoke and heat, risk of falling and risk of exposure to hazardous materials. Therefore, protection of Occupational Safety and Health (K3) for firefighters in Madiun City is crucial. This research aims to research and analyze in depth the legal aspects, implementation and challenges related to K3 protection for firefighters in Madiun City. This research is included in normative legal research with a juridical-normative approach. Research data was analyzed using qualitative methods with thematic data analysis techniques. The conclusions in this research focus on the context of K3 protection for fire fighters in the Madiun City Government which has made significant efforts but there is still room for improvement. Increasing awareness, adequate budget allocation, and increasing training and regular monitoring are important steps that need to be taken to increase the effectiveness of K3 protection and maintain the welfare of firefighting workers